Dación y alteridad - Mensch, James (2002)
“Givenness and Alterity”. One of the most difficult problems faced by phenomenology is the mystery of our self-showing. How do we show ourselves to be what we are? How do we manifest our selfhood to one another? In this article, I examine what we intend when we direct ourselves to another person. I also look at what sort of fulfillment i.e., what kind of givenness satisfies this intention. I defend the claim that to intend another person is to intend the other as exceeding our intentions. As such, theshowing which manifests the presence of the other is a kind of excessive givenness. It is a givenness that makes us aware that more is being given than we can formulate in our intentions. This awareness points to the other’s freedom. It is also a moral awareness. I conclude by arguing that our awareness of this type of givenness is our entrance into morality.